Konsep tasawuf wahdat al-wujud menurut hamzah fansuri - Azhar, Maulidul; Rohman, Slamet Mahfud (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2022)
Islam is a religion based on revelation revealed to the Prophet Muhammad through the angel Gabriel. One aspect of the doctrine of God is mysticism. In Islam, mysticism is called Tasawwuf. Western Orientalists use the word tasawwuf specifically for mysticism. The essence of Sufism is the awareness of communication and dialogue between the human spirit and God through isolation and competition. One of the schools of Sufism is Sufism whose main teaching is to get close to and even merge with God is wahdatul wujud. Wahdatul wujud is a concept or teaching that teaches about the unity of God and human form. This teaching was brought to Indonesia by a cleric named Sheikh Hamzah Fansuri, Hamzah Fansuri or Sheikh Hamzah Fansuri is a Sufi figure who plays a very important role in the historical development of Sufi thought in the archipelago, especially in the Aceh region. His thoughts on Sufism were very popular at that time. In Hamzah Fansuri's teachings, the concept of Wujudiyyah was known, which is a teaching that teaches about the existence of God. In this research the author uses a qualitative method of Library Research type, namely by clarifying and classifying. After this research, there are several results that we can get, namely Hamzah Fansuri's thoughts are: first, the Nature of Form According to Hamzah Fansuri, the form is only one even though it appears to be many. From this one form there is a skin (mazhar, external reality) and there is a content (inner reality). Second, Eka in diversity according to Hamzah Fansuri, the form is one, more precisely the ultimate form is God, al-haqq. There is no form or nothing in a state of being, other than God. A correct understanding of wujud must include not only its unity, but also its diversity. Third, the Creation of Nature The teaching of Hamzah Fansuri's old creation can be connected to the teaching of Ibn al-Arabi's creation of nature. these two teachings both argue that nature is created from existing into existence, not created from non-existing into existence. Nature is Qadim, this nature exists, created through the process of tajalli, which is the manifestation of the eternal and the final appearance.